Formulación del programa de ahorro y uso eficiente de agua para la empresa Soil tratamiento de aguas industriales Slu sucursal Colombia (2018)
Initially, the characterization of the state of consumption was carried out, which allowed to establish average monthly flows of entry and exit of the processes, as well as the losses generated by sludge. Based on the diagnosis and based on secondary information, savings alternatives were proposed for the water treatment systems operated by Soil Colombia, among which are saver devices focused on the updating of sanitary equipment, pressure washers and faucets updating (bovine benefit and pig), the design of a rainwater treatment plant (poultry benefit plant), the collection of rainwater to be treated in the water treatment plant for reuse (bovine and porcine benefit) and the reuse of water from discharge of the wastewater treatment plant, for which several alternatives are shown. Finally, a cost analysis was carried out, taking into account the equipment and instruments required for the implementation of the proposed savings alternatives in the short, medium and long term in the project, establishing the financial and environmental benefits achieved with the proposal.